L’Architecture localement bio- et géo-sourcée de Christophe Aubertin : régionaliste, biorégionaliste ? - Mathias Rollot (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
As it is nowadays quite a commonplace to criticize the extractivist, productivist and naturalist ideologies, it also became interesting to question how architecture could help to rehabilitate the idea of ressources. To do so, this essay propose an examination of a selected body of buildings from french architect Christophe Aubertin, through the filter of their « regionalist » and/or « bioregionalist » caracteristics. The research aims to produce knowledge about some of the ethical, aesthetical and political issues of our specific disciplinary use of bio-based resources.